Architectural theory and practice - Rappaport, Alexander (project baikal, 2023)
A practice is an activity that fulfils the tasks given by the administration or ordered for money. Such practice (design activity) does not need the theory of architecture. Architects-designers ignore it for a reason. The well-known paradox “there is nothing more practical than a good theory”, however, can be applied in the field of architecture. The idea of fundamental independence of theory and practice in architecture (and not only) is justified by the fact that it is impossible to know in advance how theoretical ideas will affect practice. The value of theoretical ideas is not diminished by the fact that they are not currently applied in practice and have no economic effect.